Arabic Language Competence and Metacognitive in the Study of Pragmatism Philosophy - Kafi, Fina Aunul; Wargadinata, Wildana (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This research is motivated by the need to understand the role of Arabic language competence and metacognitive skills in interpreting pragmatism philosophy. The aim of this study is to identify how the understanding of Arabic language competences with metacognitive in pragmatism philosophy This article used a qualitative approach with a literature review method. The data collection technique was derived from some literature sources and analyzed by source triangulation. The results of this study show that Arabic language competence managed metacognitively is aligned with pragmatic goals in learning Arabic. With the philosophical basis of pragmatism, learning Arabic must achieve the target of mastery, which is carried out through contextual and rational stages. The conclusion of this research is that orientation and Arabic language competence cannot be separated from philosophical understanding. One's interpretation through the philosophy of pragmatism will help in planning meaningful learning to achieve the desired goals.